Vibration serviceability assessment of GFRP pedestrian bridges. (1st April 2019) - Drygala, Izabela Joanna; Polak, Maria Anna; Dulinska, Joanna Maria
Highlights: Footbridges require attention to ensure proper functional features and comfort of use. FRP and GFRP materials became competitive solutions in the construction of bridges. In the paper numerical analysis of dynamic behaviour of GFRP footbridges is presented. Vibration serviceability due to pedestrian-induced load and traffic load was studied. Abstract: Over the past few decades, fibre-reinforced polymer (FRP) materials in general and glass-fibre-reinforced polymer (GFRP) in particular have become popular and competitive solutions in the construction of bridge objects. Because of their properties – such as high strength to weight ratios, ease of structure assembly, non-conductivity and chemical resistance – significant applications of the composite materials have been realised in the construction of footbridges in particular. In this paper, a numerical evaluation of the serviceability behaviour of two examples of composite material footbridges is presented. For the purpose of the study, it was assumed that the footbridges were made of the same composite material but they differ from each other with regard to structural geometry. The first stage of the study was the numerical estimation of the modal characteristics of the footbridges, i.e. their mode shapes and natural frequencies. The risk of the resonance phenomenon caused by pedestrian loading was then considered for both structures. In the next step of the calculations, the authors assessed the dynamic response of the footbridges to typical traffic loads; these types of load are transmitted to the structure through the ground and foundations. For numerical analysis, finite element (FE) models of the footbridges were prepared in the ABAQUS/Standard software program. The calculations included the representative time histories of the passage of a heavy goods vehicle and trains. Finally, the vibration comfort criteria for both footbridges were checked. The obtained results show that the comfort criteria are fulfilled.